Analysis of opens failure in flash multi-chip package - Balacano, Dennis Evan L. (2011)
Flash memory is a non-volatile computer storage that can be electrically erased and reprogrammed. It can come in various packages like Multi-Chip Package or MCP.MCP involves the use of multiple die stacking technology and it is extensively used in the semiconductor industry. Packages of this type are preferred because it is more cost effective and because it allows the micro-chip to have higher density. During the package qualification, a 2-die stacked MCP is triggered by high resistance or opens failure affecting 32 lots of around 38,000 units. Since there are a high number of lots affected by the opens failure and there is a meager number of research efforts tackling film adhesive void-related open failures in Flash MCP, it is the objective of this paper to find out the general cause of the opens failure in MCP, to characterize the defect that caused the failures, and to determine the source of what caused the defect and propose a mechanism of defect formation in the package. Analysis results show that the opens failure in Flash MCP is due to passivation-metal damage (PMD) defects on Die1. The PMD defect is caused by trapped silica filler that is intruded on a film adhesive void between Die 1 and Die 2. The intrusion of silica filler between Die 1 and Die can be attributed to several factos like a) presence of pre-mold delaminations that resulted to film adhesive voids, b) mold compound intrusion below the edge of Die 2 along with the high pressure during the mold process,a nd c) warping of Die 2 as a result of high temperature during mold process. To lessen or eliminate the formation of permanent film adhesive voids, Die Attach tool parameters must be optimized.
October 2011"
Thesis (M.S. Materials Science and Engineering)--University of the Philippines, Diliman.
Keywords: Virtual storage (Computer science).; Flash memory